Treatment-resistant bipolar depression: a STEP-BD equipoise randomized effectiveness trial of antidepressant augmentation with lamotrigine, inositol, or risperidone. - Nierenberg, A; Ostacher, M; Calabrese, JR; Ketter, T; Marangell, L; Miklowitz, D; Miyahara, S; Bauer, MS; Thase, M; Wisniewski, SR; Sachs, G (2006)
OBJECTIVE: Clinicians have few evidence-based options for the management of treatment-resistant bipolar depression. This study represents the first randomized trial of competing options for treatment-resistant bipolar depression and assesses the effectiveness and safety of antidepressant augmentation with lamotrigine, inositol, and risperidone. METHOD: Participants (N=66) were patients with bipolar I or bipolar II disorder enrolled in the NIMH Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD). All patients were in a current major depressive episode that was nonresponsive to a combination of adequate doses of established mood stabilizers plus at least one antidepressant. Patients were randomly assigned to open-label adjunctive treatment with lamotrigine, inositol, or risperidone for up to 16 weeks. The primary outcome measure was the rate of recovery, defined as no more than two symptoms meeting DSM-IV threshold criteria for a mood episode and no significant symptoms present for 8 weeks. RESULTS: No significant between-group differences were seen when any pair of treatments were compared on the primary outcome measure. However, the recovery rate with lamotrigine was 23.8%, whereas the recovery rates with inositol and risperidone were 17.4% and 4.6%, respectively. Patients receiving lamotrigine had lower depression ratings and Clinical Global Impression severity scores as well as greater Global Assessment of Functioning scores compared with those receiving inositol and risperidone. CONCLUSIONS: No differences were found in primary pairwise comparison analyses of open-label augmentation with lamotrigine, inositol, or risperidone. Post hoc secondary analyses suggest that lamotrigine may be superior to inositol and risperidone in improving treatment-resistant bipolar depression.